Advancement in artificial intelligence for on-farm fruit sorting and transportation - Zhou, Zheng; Zahid, Umair; Majeed, Yaqoob; Nisha,; Mustafa, Sadaf; Sajjad, Muhammad Muzzammil; Butt, Hafiz Danish; Fu, Longsheng (Frontiers in Plant Science, 2023)
On-farm sorting and transportation for fruits in postharvest stage includes sorting out defective products, grading into categories based on quality, distributing into bins, and carrying bins to field collecting station. Advancement in artificial intelligence (AI) can speed up on-farm sorting and transportation with high accuracy and robustness and significantly reduce postharvest losses. The primary objective of this literature review is to present an overview to present a critical analysis and identify the challenges and opportunities of AI applications for on-farm sorting and transportation, with a focus on fruits. Challenges of on-farm sorting and transportation were discussed to specify the role for AI. Sensors and techniques for data acquisition were investigated to exhibit the tasks that the AI models have tackled for on-farm sorting and transportation. AI models proposed in previous studies were compared to investigate the adequate approaches for on-farm g sorting and transportation. Finally, advantages and limitations of utilizing AI has been discussed and in-depth analysis was provided to identify the future research directions. We anticipate that this survey will lead the path for further study into implementing automated systems for on-farm fruit sorting and transportation.